Factors related to maternal awareness in administering the Human Papillomavirus (HPV) vaccine to children aged 9 - 14 years at the South City Health Center - Fadillah Amalia Yusuf; Laksmyn Kadir; Suardi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Cervical cancer is one of the leading causes of death in women, which is mostly caused by Human Papillomavirus (HPV) infection. The HPV vaccine is one of the effective prevention efforts, but maternal awareness in giving vaccines to children is still a challenge. This study aims to analyze the relationship between access to information, the role of health workers, and family support with maternal awareness of HPV vaccine administration to girls aged 9-14 years in the working area of the South City Health Center. This study uses an observational analytical method with a cross sectional approach. The research population was 166 mothers with a sample of 117 respondents obtained using purposive sampling techniques. Data were collected using questionnaires and analyzed univariate and bivariate using the Chi-Square test. The results showed that most of the respondents had good awareness (75.2%). Respondents' access to information was mostly in the poor category (65.8%), while the role of health workers (66.7%) and family support (56.4%) was in the good category. The results of the analysis showed that there was a significant relationship between access to information (p = 0.000), the role of health workers (p = 0.000), and family support (p = 0.000) and maternal awareness of HPV vaccine administration. The conclusion of this study shows that access to information, the role of health workers, and family support are significantly related to maternal awareness of HPV vaccine administration.